The Impact of Femoral Component Cementation on Fracture and Mortality Risk in Elective Total Hip Arthroplasty: Analysis from a National Medicare Sample. (16th March 2022) - Edelstein, Adam I.; Hume, Eric L.; Pezzin, Liliana E.; McGinley, Emily L.; Dillingham, Timothy R.
Abstract : Background: Complications following elective total hip arthroplasty (THA) are rare but potentially devastating. The impact of femoral component cementation on the risk of periprosthetic femoral fractures and early perioperative death has not been studied in a nationally representative population in the United States. Methods: Elective primary THAs performed with or without cement among elderly patients were identified from Medicare claims from 2017 to 2018. We performed separate nested case-control analyses matched 1:2 on age, sex, race/ethnicity, comorbidities, payment model, census division of facility, and exposure time and compared fixation mode between (1) groups with and without 90-day periprosthetic femoral fracture and (2) groups with and without 30-day mortality. Results: A total of 118, 675 THAs were included. The 90-day periprosthetic femoral fracture rate was 2.0%, and the 30-day mortality rate was 0.18%. Cases were successfully matched. The risk of periprosthetic femoral fracture was significantly lower among female patients with cement fixation compared with matched controls with cementless fixation (OR = 0.83; 95% CI, 0.69 to 1.00; p = 0.05); this finding was not evident among male patients (p = 0.94). In contrast, the 30-day mortality risk was higher among male patients with cement fixation compared with matched controls with cementless fixation (OR = 2.09; 95% CI, 1.12 to 3.87; p = 0.02). The association between cement usage and mortality among female patients almost reached significance (OR = 1.74; 95% CI, 0.98 to 3.11; p = 0.06). Conclusions: In elderly patients managed with THA, cemented stems were associated with lower rates of periprosthetic femoral fracture among female patients but not male patients. The association between cemented stems and higher rates of 30-day mortality was significant for male patients and almost reached significance for female patients, although the absolute rates of mortality were very low. For surgeons who can competently perform THA with cement, our data support the use of a cemented stem to avoid periprosthetic femoral fracture in elderly female patients. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.